Highly sensitive thermal damage sensors for polymer composites: time temperature indicator based on thermochromic fluorescence turn-on response. (28th July 2017) - Toivola, Ryan; Howie, Tucker; Yang, Jeffrey; Lai, Po-Ni; Shi, Zhengwei; Jang, Sei-Hum; Jen, Alex K-Y; Flinn, Brian D
Abstract: Carbon fiber epoxy composites have become prevalent in a variety of industries, especially in aerospace. The significant non-destructive evaluation (NDE) challenges of composites require new solutions, especially in detecting the onset of thermal damage. This work proposes the use of thermochromic fluorescent molecules dispersed in the composites as sensors for such detection. A molecule has been developed which transitions from a colorless, non-fluorescent state to a colorful, highly fluorescent state when exposed to temperature-time combinations that can cause damage in composites. This molecule dispersed in polymer composites of epoxy and PDMS matrices shows unique activation kinetics that can be used to quantitatively simulate the degradation kinetics of aerospace epoxies. The novel sensor materials based on the thermochromic activation of fluorescence can provide highly efficient and widely applicable NDE materials and techniques for carbon fiber epoxy composites.